Short/long-term cryopreservation prior to comet assay of whole-blood leukocytes and in vitro-cultured lung fibroblasts. (2nd September 2021) - Volobaev, V.; Bach, S.; Shchetnikova, E.; Vdovina, E.; Rosinskiy, A.; Larionov, A.
Abstract: Single-cell gel electrophoresis (comet assay) is a valuable test that can be used in ecotoxicological, epidemiological, and biomonitoring contexts. We assessed the effects of short- (without cryopreservation) and long-term (with cryopreservation) storage of DMEM-cultivated human peripheral blood leukocytes (HPBLs) and a human lung fibroblast cell line (FLECH-104) on comet assay results. Samples were stored for 6 or 24 h at room temperature (23°С) or 4 °C and frozen at −80 °C or −196 °C for 1, 2, or 4 weeks. Short-term storage led to significant increases in the comet tail intensity (TI) and Olive tail moment (OTM) in HPBL and FLECH-104 samples. Freezing FLECH-104 samples at −80°С and −196°С resulted in TI mean increases, with no differences in OTM. All frozen HPBL samples did not exhibit significant increases in TI or OTM, and instead exhibited a slight decrease in TI versus the control at both −80 °C and −196 °C. Increased frequency of highly damaged cells was observed in FLECH-104 and HPBL cultures during both short-term storage and after freezing, which may indicate a significant destructive effect. Therefore, freezing of cell cultures and whole blood according to our protocol is not recommended.